The role of lifetime periods in the organisation of episodic memories. Issue 8 (14th September 2019) - Mace, John H.; Unlu, Merve
ABSTRACT: Research on the nature of episodic memory associations has suggested that episodic memories are associated by conceptual knowledge, where memories cluster around the same content (e.g. memories about the same people) or general-event knowledge, where memories cluster around extended events (e.g. a holiday in London), repeated events (e.g. Sunday walks in the park), or causally related events (i.e. where one event leads to another). Research has also suggested that episodic memories are associated by lifetime periods (e.g. when I was in high school), where memories cluster within lifetime periods. However, it is unclear whether episodic memories can be associated solely by lifetime periods, or if such associations are subordinate to conceptual or general-event associations. To answer this question, we reanalysed a large sample of involuntary memory chains (Mace, J. H., Clevinger, A. M., & Bernas, R. S. (2013). Involuntary memory chains: What do they tell us about autobiographical memory organisation? Memory, 21, 324–335). The results of this analysis suggested that lifetime periods associations are subordinate to conceptual and general-event associations, as lifetime periods were found to cluster within the latter two associations. The potential functions of this organisation are discussed.